Alterations in the Erythrocyte Antioxidant Enzyme Levels in Experimental Sepsis: Role of Melatonin - Mükerrem Betül Yerer (De Gruyter, 2006)
The organisms possess antioxidant defense systems, including antioxidant enzymessuch as glutathione peroxidase (GSH-Px), superoxide dismutase (SOD) and catalase(CAT), to deal with the reactive oxygen species generated in physiological andpathophysiological situations. Melatonin was recently shown to act as a putativeantioxidant in the pathology of many diseases. The aim of this study was to investigatethe effects of melatonin on antioxidant enzyme activities in septic rats. Swiss albinomale rats weighing 250-300 g were randomly divided into 4 groups comprising of10 animals in each group. The first group was the control group. The second groupwas given melatonin (10 mg/kg) and third group was given only lipopolysaccharide(LPS, 10 mg/kg) by i.p. injection. The fourth group received melatonin (10 mg/kg,i.p.) after 4 hours than the LPS administration. All the rats in 4 groups were killedat the end of the 6th hour after the first injection. The erythrocytes isolated fromthe whole blood were used to evaluate the GSH-Px, SOD and CAT activities. Asa result, GSH-Px, SOD were significantly stimulated in sepsis with LPS treatmentwhere CAT activities were decreased. Furthermore, GSH-Px and SOD activitieswere triggered significantly by melatonin administration, whereas the CAT activityreduced. These findings reveal that melatonin stimulates the antioxidant enzymeactivities in the erythrocytes of septic rats, but further information is required tofind out its inhibitory effects on the CAT activity.